FOREST ACCOUNTING AT FAIR VALUE: AN EVALUATION OF STRENGTHS AND POSSIBILITIES TO MINIMISE SHORTCOMINGS - Budrionytė, Ramunė; Subačienė, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The accounting standards provide options for different accounting methods to be deployed in accounting of certain assets. However, in other cases, only one of the specified methods should be applied. The forest (stands), the main resource of forestry enterprises, is also attributed to this category of assets, which, according to the standard IAS 41 Agriculture, should be accounted for only at fair value. The aim of the paper is to identify the strengths and shortcomings of applying the concept of fair value to forest financial accounting and to evaluate the possibilities to minimise the disadvantages. The study examines the scholarly literature and deploys the theoretical methods of comparative analysis, critical evaluation, systematisation, generalisation. The empirical research involves the document content analysis, expert assessment methods.The paper examines the issues of applying the fair value concept to forestry accounting: forest valuation at fair value in financial statements reflects the forest biological transformation and the impact of market price changes on the value of the forest. However, the main disadvantage of this method is the fact that the forest often does not have an active market with quoted prices. Thus, its fair value is determined using different valuation methods, often based on subjective assumptions resulting in financial information which can be unreliable and difficult to verify. Furthermore, the profit and loss accounts including the recognition of the change in the fair value of the forest to be sold in the forthcoming decades are not only doubtful, but may also lead to false interpretations of the financial indicators and contradict to the prudence principle. Based on the conclusions of expert evaluation of certain aspects of forest accounting at fair value, the research study offers a modified method of forest accounting at fair value which facilitates minimisation of the shortcomings.